3. Asymmetric hypsarrythmia: An insight into the pathophysiology of infantile spasms. A retrospective cohort. Issue 11 (November 2017) - Desnous, B.; Arbour, M.; Nguyen, H.S.; Lortie, A.; Chartrand, D.; Rossignol, E.; Diadori, P.; Major, P.; Carmant, L.; Birca, A.
Abstract : Infantile spasms (IS) is a catastrophic epilepsy where treatment precocity improves outcome. Previous studies demonstrated an association between asymmetric hypsarrhythmia on EEG and ipsilateral hemispheric lesions on MRI, suggesting a possible role of cortical lesions in the initiation of IS. Epileptiform abnormalities appearing during early infancy have also been linked to IS emergence. We hypothesized that focal lateralized EEG abnormalities during the prehyspasrrhythmic period will be associated with asymmetric hypsarrhythmia at IS onset. We recruited a retrospective cohort of 80 infants, 7.4 ± 3.6 months old at the onset of hypsarrhythmia and IS, admitted to Sainte-Justine Hospital between 2007 and 2016. Seven infants showed an asymmetric hypsarrhythmia pattern and, as expected, all of them had lateralized lesions on MRI. Of the remaining 73, 42 had abnormal MRI, but only 3 infants had lateralized lesions (100% vs 7.1%, p < 0.01). Thirty-four patients had pre-hypsarrhythmic EEG recordings at the age of 4.6 ± 2.6 months, 3 ± 2 months before IS onset, including four infants with asymmetric hypsarrhythmia. Five infants had no pre-hypsarrhythmic epileptiform abnormalities. Six had focal lateralized, while 23 multifocal abnormalities. The proportion of patients with focal abnormalities was higher in those who developed asymmetric compared to symmetric hypsarrhythmia (50% vs 13.3%, p < 0.05). Our data confirm the link between asymmetric hypsarrhythmia and lateralized MRI lesions. Moreover, we show that focal lateralized EEG abnormalities precede asymmetric hypsarrythmia, which supports the involvement of cerebral cortex in the IS genesis. More sensitive EEG biomarkers of high IS risk may help developing preventative treatments that will improve outcomes in IS.